Photogrammetry: methods of survey and applications on restoration works - Genin, S. M. (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
This paper presents diverse methods of photogrammetric surveys and applications in restoration works. It compares the methods of survey and highlights their advantages for each specific project. All the methods used showed the great advantage of photogrammetry, compared with the traditional method of survey. There is a great reduction of working hours (field and office). The restitution may be drawn up at any time, with the required degree of rigour, and may be more or less detailed depending on the needs of the Project, case of the dismantling of Cais das Colunas, in Lisbon. The single-image photogrammetry allows the restitution of flat elements, without information on their depth, which is ideal for surveying facades. In the Conservation project of the vaults of Jerónimos monastery church, the traditional stereophotogrammetry had the advantage of stereoscopic vision, allowing a careful observation of the details, anomalies of the construction and a precise diagnostic in situ. Photogrammetry of multiple images is a much faster method for obtaining the 3D model, through a dense cloud of points, which is the most commonly used in recent restoration projects, for heritage documentation and three-dimensional visualisation of the object. This last method was used to survey the church facade of the monastery of Alcobaça. The survey of São Miguel – o - Anjo lighthouse in Porto, and all the other cases, proved that photogrammetric restitution allows a detailed mapping of the construction, necessary for a correct diagnostic of the anomalies to support the Conservation Project.